Combined exposure to cyanobacterial biomass, lead and the Newcastle virus enhances avian toxicity - Pikula, Jiri; Bandouchova, Hana; Hilscherova, Klara; Paskova, Veronika; Sedlackova, Jana; Adamovsky, Ondrej; Knotkova, Zora; Lany, Petr; Machat, Jiri; Marsalek, Blahoslav; Novotny, Ladislav; Pohanka, Miroslav; et al. (The Science of the total environment, 2010)
Under environmental conditions, wild birds can be exposed to multiple stressors including natural toxins, anthropogenic pollutants and infectious agents at the same time. This experimental study was successful in testing the hypothesis that adverse effects of cyanotoxins, heavy metals and a non-pathogenic immunological challenge combine to enhance avian toxicity. Mortality occurred in combined exposures to naturally occurring cyanobacterial biomass and lead shots, lead shots and Newcastle vaccination as well as in single lead shot exposure. Mostly acute effects around day 10 were observed. On day 30 of exposure, there were no differences in the liver accumulation of lead in single and combined exposure groups. Interestingly, liver microcystin levels were elevated in birds co-exposed to cyanobacterial biomass together with lead or lead and the Newcastle virus. Significant differences in body weights between all Pb-exposed and Pb-non-exposed birds were found on days 10 and 20. Single exposure to cyanobacterial biomass resulted in hepatic vacuolar dystrophy, whereas co-exposure with lead led to more severe granular dystrophy. Haematological changes were associated with lead exposure, in particular. Biochemical analysis revealed a decrease in glucose and an increase in lactate dehydrogenase in single and combined cyanobacterial and lead exposures, which also showed a decreased antibody response to vaccination. The combined exposure of experimental birds to sub-lethal doses of individual stressors is ecologically realistic. It brings together new pieces of knowledge on avian health. In light of this study, investigators of wild bird die-offs should be circumspect when evaluating findings of low concentrations of contaminants that would not result in mortality on a separate basis. As such it has implications for wildlife biologists, veterinarians and conservationists of avian biodiversity.
Keywords: biomasa; olovo; mikrocystiny; Lead; Male; newcastleská nemoc; Microcystins; Cyanobacteria; Newcastle Disease; Biomass; látky znečišťující životní prostředí; Disease Susceptibility; mužské pohlaví; sinice; nemoci ptáků; Animals; játra; zvířata; Bird Diseases; Environmental Exposure; Environmental Pollutants; Liver; náchylnost k nemoci; Coturnix; vystavení vlivu životního prostředí